The Effectiveness of Inputs in Primary Education : Insights from Recent Student Surveys for Sub-Saharan Africa - Fehrler, Sebastian; Michaelowa, Katharina; Wechtler, Annika (My University, 2009)
With SACMEQ and PASEC there are now two large data bases available on student achievement, socio-economic background and school and teacher characteristics in both anglophone and francophone sub-Saharan Africa. A joint analysis of PASEC and SACMEQ in a common education production function framework allows us to estimate the impact of educational inputs on student achievement in 21 sub-Saharan African countries and to compare our results with those of earlier empirical studies for education systems in Africa and other world regions. In our analysis we focus on school equipment, teacher quality and class organisation. The issue of teacher and student incentives cannot be adequately addressed with the given data. Our results are based on a traditional retrospective analysis of student achievement in PASEC and SACMEQ countries. In contrast to the ‘nothing works’ result from most industrialized countries’ studies we find robust positive correlations of achievement test scores and the possession of textbooks and negative correlations with teaching in shifts. The most striking result is the weak or even absent correlation of achievement test scores and teacher education and professional training. However, some differences between francophone and anglophone education systems can be observed in this context if differences in the sampling methodology are duly taken into account.
Keywords: education, sub-sahara africa, education production function; 330